Neuronal Replacement in Stem Cell Therapy for Stroke: Filling the Gap - Palma-Tortosa, Sara; Coll-San Martin, Berta; Kokaia, Zaal; Tornero, Daniel (Frontiers in Cell and Developmental Biology, 2021)
Stem cell therapy using human skin-derived neural precursors holds much promise for the treatment of stroke patients. Two main mechanisms have been proposed to give rise to the improved recovery in animal models of stroke after transplantation of these cells. First, the so called by-stander effect, which could modulate the environment during early phases after brain tissue damage, resulting in moderate improvements in the outcome of the insult. Second, the neuronal replacement and functional integration of grafted cells into the impaired brain circuitry, which will result in optimum long-term structural and functional repair. Recently developed sophisticated research tools like optogenetic control of neuronal activity and rabies virus monosynaptic tracing, among others, have made it possible to provide solid evidence about the functional integration of grafted cells and its contribution to improved recovery in animal models of brain damage. Moreover, previous clinical trials in patients with Parkinson’s Disease represent a proof of principle that stem cell-based neuronal replacement could work in humans. Our studies with in vivo and ex vivo transplantation of human skin-derived cells neurons in animal model of stroke and organotypic cultures of adult human cortex, respectively, also support the hypothesis that human somatic cells reprogrammed into neurons can get integrated in the human lesioned neuronal circuitry. In the present short review, we summarized our data and recent studies from other groups supporting the above hypothesis and opening new avenues for development of the future clinical applications.